Kepemimpinan Kiai dalam Resolusi Konflik Pesantren dengan Masyarakat (Studi Multikasus Pesantren Itiqlal Buleleng dan Pesantren Bali Bina Insani Tabanan) - Haya Haya (MOMENTUM : Jurnal Sosial dan Keagamaan, 2021)
Abstract The idea of ​​pesantren conflict resolution as a new perspective rise from a view that conflict does not only occur in society on a macro scale, but also affects the world of Islamic education, especially pesantren. At the same time, Kiai has a significant role in curative behavior and initiative to build a public trust in Bali the trigger for the peaceful development of Islam in Bali. Thus, the kiai's actions in conflict resolution through pesantren related to the global, regional and local areas. Conflicts in several islamic countries rises to a gloomy view of pesantren. The people in the West view that pesantren as a hotbed for terrorists. Research of pesantren in Buleleng and Tabanan shows that people have a less understanding about pesantren, so they show the understanding of anti-tolerance and anti-globalization. Those view based on the behavior of non-mainstream who seem closed and do not adapt to the local culture in Bali. They view related to a rigid of Islamic view that different from them as heresy and even infidels. This is evidenced by the case of the Ahmadiyya Jamaat's of several people in Buleleng. The existence of pesantren are closely related to strategic environment, both global, national and local. In the global perspective, pesantren received international attention. In 2016, the Bali Bina Insani was visited by ministres of an international congress on tolerance. They understood that the values ​​of pesantren are directly related to the mission of world peace developement by the United Nations (UN). The tolerance developed by pesantren is being the antidote of conflicts in Islamic countries and other countries in the world.